Development of novel strategies for detection and treatment of cancer - Samarakoon, Thilani Nishanthika (Kansas State University, 2012)
Cancer is one of the leading causes of death in the world. Billions of dollars are spent to treat cancer every year. This clearly shows the need for developing improved treatment techniques that are affordable to every person. Early diagnosis and imaging of tumors is equally important for the battle against this disease. This dissertation will discuss new approaches for discovering and developing novel detection and treatment techniques for cancer using organic ligands, and Fe/Fe3O4 core/shell magnetic nanoparticles. A series of o-phenylenediamine derivatives with nitro-, methyl- and chloro- substituents were synthesized and studied their ability to act as anticancer agents by using steady-state, UV/Vis-, and fluorescence spectroscopy. In the absence of zinc(II), intercalation with DNA is the most probable mode of interaction. Upon addition of zinc(II), DNA-surface binding of the supramolecular aggregates was observed. The interaction of the supramolecular (-ligand-Zn2+-)n aggregates with MDA 231 breast cancer cells led to significant cell death in the presence of UVA at λ=313 nm displaying their potential as anticancer agents. Bimagnetic Fe/Fe3O4 core/shell nanoparticles (MNPs) were designed for cancer targeting after intratumoral or intravenous administration. Their inorganic center was protected by dopamine-oligoethylene glycol ligands. TCPP (4-tetracarboxyphenyl porphyrin), a fluorescent dye, was attached to the dopamine-oligoethylene glycol ligands. These modified nanoparticles have the ability to selectively accumulate within the cancerous cells. They are suitable candidates for local hyperthermia treatment. We have observed a temperature increase of 11 ºC in live mice when subcutaneously injecting the MNPs at the cancer site and applying an alternating magnetic field The system is also suitable for Magnetic Resonance Imaging (MRI), which is a diagnostic tool to obtain images of the tumors. Our superparamagnetic iron oxide nanoparticles have the ability to function as T1 weighted imaging agents or positive contrasting agents. We were able to image tumors in mice using MRI. Various proteases are over-expressed by numerous cancer cell lines and, therefore, of diagnostic value. Our diagnostic nanoplatforms, designed for the measurement of protease activities in various body fluids (blood, saliva, and urine), comprise Fe/Fe3O4 core/shell nanoparticles featuring consensus sequences, which are specific for the target protease. Linked to the consensus sequence is a fluorescent organic dye (e.g. TCPP). Cleavage of the sequence by the target protease can be detected as a significant increase in fluorescence occurring from TCPP. We were able to correlate our diagnostic results with cancer prognosis.
Keywords: Urokinase plasmin activator (UPA); Matrix metalloproteinases (MMPs); Fluorescence assays; Cancer detection; Cancer treatment; Hyperthermia; Chemistry (0485)